Religion as a key front of Russian aggression against Ukraine - Vasin, Maksym (War in Ukraine, 2025)
The Russian aggression against Ukraine, which has been going on for more than ten years, actively includes the religious front. Fully controlled by the Kremlin, Russian religious centers and their leaders have de facto been transformed into political or governmental structures. They are involved in spreading Kremlin propaganda that fuels hatred of the Ukrainian nation and incites Russian citizens to continue this unjust war. Many Russian religious leaders can be considered accomplices in numerous war crimes committed by the Russian army in Ukraine. In response, the Ukrainian parliament passed law No. 3894-IX. The law seeks to ban the activities of Russian religious centers in Ukraine because they have become part of Putin’s dictatorial regime. This paper elaborates on the religious dimension of the Russian invasion of Ukraine from different perspectives. The author analyses the recent events in Ukraine and Russia by examining the changes in religious life in the historical and political contexts of both countries.